Public Awareness, Attitudes, and First-Aid Measures on Epilepsy in Tehran - Abbasi-Kangevari, Mohsen; Kolahi, Ali-Asghar; Farsar, Ahmad Reza; Kermaniranjbar, Saeid (Iranian Journal of Child Neurology, 2019)
Background: People with epilepsy generally encounter misconceptions and negative attitudes about different aspects of the disease. They are also prone to physical injuries during seizures. Lack of awareness about first-aid measures results in taking inappropriate first-aid measures. The objective of this survey was to determine public awareness, attitudes, and first-aid measures about epilepsy in Tehran. Methods: This population-based cross-sectional survey was conducted during December 2016 to May 2017 throughout Tehran. Random stratified cluster sampling was used. Data were collected through interviews using a questionnaire. The awareness section included general awareness, causes, symptoms, seizure triggers, first-aid measures, and recommended treatments. The Likert scale was used for the attitudes section which included 20 statements. The answers about first-aid measures were categorized as helpful, or harmful. Results: A total of 833 adults participated in the survey. The level of total awareness score of 41 (4.9%) participants was very good, 194 (23.3%) good, 255 (30.6%) fair, 210 (25.2%) low, and 133(16.0%) very low. The mean (SD) score about general awareness was 4.6 (3.0), range=0 to 11; causes 5.8 (3.4), range=0 to 13; symptoms of seizures 7.0 (4.0), range=0 to 13; first-aid measures 7.5 (3.4), range=0 to 14. Among all participants, 260 (31.2%), named at least one superstitious cause for epilepsy. Attitudes were generally positive except for marriage and having kids. The level of first-aid measures score of 74(42.5) was very good, 79(45.4) good, and 21(12.1) low. Conclusion: The awareness of people of Tehran about epilepsy was insufficient, attitudes were generally positive but rather conservative, and first-aid measures at the last witnessed seizure were fairly helpful.